Boletín de la Real Academia Española: tomo 30 (1950), tomo 31 (1951). - Lope Blanch, Juan M. (El Colegio de México, 1957)
Se reseñó: Boletín de la Real Academia Española: tomo 30 (1950), tomo 31 (1951).